Paper 59: Comparison of Knotless versus Knotted Suture Anchors in the Arthroscopic Management of Adolescent Shoulder Instability. Issue 7 (30th July 2022) - Ghetti, Claudio; Michelin, Richard; Fogleman, Sarah; Gornick, Bryn; Carroll, Alyssa; Edmonds, Eric; Schlechter, John
Objectives: Shoulder instability among adolescent athletes remains a complex challenge with high recurrence rates. Knotted suture anchors have provided consistently reliable biomechanical and clinical results. In recent years, the advent of the knotless suture anchor technology has come with proposed advantages of minimizing technical difficulty and knot migration, as well as reducing subsequent intra-articular cartilage irritation and damage. While several studies have analyzed the utility of knotless suture anchors in the adult population, to our knowledge, there has not been a direct comparison within this more at risk for surgical failure adolescent population. The purpose of this study was to compare the effect of knotted versus knotless suture anchor use on postoperative outcomes of arthroscopic shoulder instability surgery in the adolescent athlete. Methods: A multicenter comparative cohort was conducted of patients that underwent primary arthroscopic shoulder labral repair with suture anchor implants for shoulder instability between June 2015 and November 2017. Additional inclusion criteria included patient age <20 years and minimum follow up duration of 3.5 years. Data collected included demographics, number and type of suture anchor (knotted or knotless), number of instability events, type of instability, and presence of bony Bankart lesions. All included patients had <20% glenoid bone loss at the time of surgery. Type of instability was also recorded and was classified as either: anterior, posterior, or multidirectional (MDI). The primary outcome measure was surgical failure, which was defined as any recurrent instability event post-surgery. Incidence of secondary surgery (including revision or need for additional procedure), surgical times, and return to sport (RTS) data were also recorded. Patient-reported outcomes were evaluated using the Pediatric and Adolescent Shoulder Survey (PASS), SANE (Single Assessment Numeric Evaluation) scores, and the Quick version of Disabilities of the Arm, Shoulder and Hand (QuickDASH) survey. Results: Eighty-eight shoulders (54 male, 34 female) from 84 patients met inclusion criteria and were analyzed. 43 received knotless anchors and 45 received knotted anchors. Mean follow-up duration was 4.5 years (range, 3.5-6 years) for the knotless cohort and 4.8 years (range, 3.7-5.8 years) for the knotted cohort. Demographics and type of instability by suture anchor type is shown in Table 1. Surgical failure rate was significantly lower in the knotless cohort (knotless, 16%; knotted, 53%; P <.001). Patients with knotless suture anchors reported significantly higher mean PASS scores (knotless, 90.2; knotted, 81.3; P =.002 ) . There was no difference in both RTS rates (knotless, 86%; knotted, 68%; P =.055) and incidence of repeat surgery between cohorts (knotless, 9%; knotted, 13%; P =.551). Surgical times, SANE scores, and QuickDASH scores were available for approximately three-quarters of shoulders (total, 65; knotless, 36; knotted, 29) in the cohort. Mean surgical time was approximately 18 minutes shorter for knotless anchors (knotless, 84.4 minutes; knotted, 102.7 minutes; P <.001). SANE scores were significantly higher in the knotless group (knotless, 88.8; knotted, 74.3; P =0.004). QuickDASH scores, of which a lower score is considered a better outcome, were not different (knotless, 5.7; knotted, 11.4; P =.063). Conclusions: Our initial intent was to demonstrate that knotless anchors would be just as successful as labral repairs with knotted anchors, but our results indicate several promising advantages, including: better patient reported outcome measures (PASS and SANE scores), reduced surgical times, and lower failure rates at a mean 4.5 years. There were some non-significant differences in the two cohorts regarding the type of instability that likely contributed to the differences in the number of anchors utilized. Future studies with larger sample sizes may serve to confirm our observed benefits associated with knotless anchors. In summary, the utilization of knotless suture anchor constructs for the repair of labral tears in adolescent shoulder instability may be safely considered with potentially improved outcomes over knotted anchors. Table 1. Demographic characteristics of included patients